Clinical Sensitivity of Cystic Fibrosis Mutation Panels in a Diverse Population. Issue 2 (2nd December 2015) - Hughes, Erin E.; Stevens, Colleen F.; Saavedra‐Matiz, Carlos A.; Tavakoli, Norma P.; Krein, Lea M.; Parker, April; Zhang, Zhen; Maloney, Breanne; Vogel, Beth; DeCelie‐Germana, Joan; Kier, Catherine; Anbar, Ran D.; et al.
Abstract : Cystic Fibrosis (CF), one of the most common recessive diseases in North America, is tested at birth in the US via newborn screening. In this study, we validated use of DNA extracted from newborn screening dried blood spots on Illumina's MiSeqDx next generation sequencing platform. A comparison of CF mutation panels in the diverse New York CF population demonstrated varied clinical sensitivity, which differed by race/ethnicity. ABSTRACT: Infants are screened for cystic fibrosis (CF) in New York State (NYS) using an IRT‐DNA algorithm. The purpose of this study was to validate and assess clinical validity of the US FDA‐cleared Illumina MiSeqDx CF 139‐Variant Assay (139‐VA) in the diverse NYS CF population. The study included 439 infants with CF identified via newborn screening (NBS) from 2002 to 2012. All had been screened using the Abbott Molecular CF Genotyping Assay or the Hologic InPlex CF Molecular Test. All with CF and zero or one mutation were tested using the 139‐VA. DNA extracted from dried blood spots was reliably and accurately genotyped using the 139‐VA. Sixty‐three additional mutations were identified. Clinical sensitivity of three panels ranged from 76.2% (23 mutations recommended for screening by ACMG/ACOG) to 79.7% (current NYS 39‐mutation InPlex panel), up to 86.0% for the 139‐VA. For all, sensitivity was highest in Whites and lowest in the Black population. Although the sample size was small, there was a nearly 20% increase in sensitivity for the Black CF population using the 139‐VA (68.2%) over the ACMG/ACOG and InPlex panels (both 50.0%). Overall, the 139‐VA is more sensitive than other commercially available panels, and could be considered for NBS, clinical, or research laboratories conducting CF screening.